Islamic Legal Perspectives on the Protection of Unborn Children from Unmarried Mothers: An Analysis of Maslahah Mursalah - Muzayyanah Khaliq (Al-Qalam Institute, 2025)
The increasing complexity of non-marital pregnancy raises urgent legal and ethical questions regarding the protection of unborn children within Islamic law. This study aims to analyze Islamic legal perspectives on safeguarding unborn children from unmarried mothers through the framework of maslahah mursalah. Employing a qualitative, normative-juridical design and limited empirical inquiry, the research draws on classical and contemporary fiqh literature and semi-structured interviews with six experts in Islamic law, the judiciary, and child rights. The findings reveal that child protection from conception constitutes a daruriyyah interest under hifz al-nafs and hifz al-nasl, and that maslahat-based reasoning allows financial support, recognition of legal identity, and anti-discrimination measures without negating classical lineage doctrine. The study’s novelty lies in integrating maqasid theory with empirical insights to reformulate the discourse on child protection. It recommends contextual ijtihad and policy harmonization to ensure non-discriminatory legal safeguards consistent with Sharia objectives.